Aberrant pace of cortical neuron development in brain organoids from patients with 22q11.2 deletion syndrome-associated schizophrenia - Sneha B. Rao; Zhixiong Sun; Francesco Brundu; Yannan Chen; Yan Sun; Huixiang Zhu; Robert J. Shprintzen; Raju Tomer; Raul Rabadan; Kam W. Leong; Sander Markx; Steven A. Kushner; et al. (Nature Communications)
Abstract Children and adults with 22q11.2 deletion syndrome (22q11.2DS) experience cognitive and emotional challenges and face a markedly increased risk for schizophrenia (SCZ), yet how this deletion alters early human brain development remains unclear. Using cerebral cortex organoids derived from individuals with 22q11.2DS and SCZ, we identify cell-type-specific developmental abnormalities. Single-cell RNA sequencing and experimental validation reveal delayed cortical neuron maturation, with increased neural progenitor proliferation and a reduced proportion of more mature neurons. We observe disrupted molecular programs linked to neuronal maturation, sparser neurites, and blunted glutamate-induced Ca²⁺ responses. The aberrant transcriptional profile is enriched for neuropsychiatric risk genes. MicroRNA profiling suggests that DGCR8 haploinsufficiency contributes to these effects via dysregulation of genes that control the pace of maturation. Protein-protein interaction network analysis highlights complementary roles for additional deleted genes. Our study reveals consistent developmental and molecular defects caused by 22q11.2 deletions, offering insights into disease mechanisms and therapeutic strategies.